2015
DOI: 10.1038/ejhg.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

DYRK1A haploinsufficiency causes a new recognizable syndrome with microcephaly, intellectual disability, speech impairment, and distinct facies

Abstract: Dual-specificity tyrosine-(Y)-phosphorylation-regulated kinase 1 A (DYRK1A ) is a highly conserved gene located in the Down syndrome critical region. It has an important role in early development and regulation of neuronal proliferation. Microdeletions of chromosome 21q22.12q22.3 that include DYRK1A (21q22.13) are rare and only a few pathogenic single-nucleotide variants (SNVs) in the DYRK1A gene have been described, so as of yet, the landscape of DYRK1A disruptions and their associated phenotype has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 45 publications
6
117
0
1
Order By: Relevance
“…Interestingly, the targeted deletion of one allele of the kinase Dyrk1a in mice resulted in decreased brain volume, and the authors observed reduced neuronal size and dendritic complexity, similar to our observations in 16pdup neurons(Benavides-Piccione et al, 2005; Fotaki et al, 2002). This kinase is involved in regulation of the PI3K/AKT and Ras/MAPK pathways and hence it is likely that its disruption may result in aberrant neuronal differentiation via dysregulation of these pathways(Ji et al, 2015). However, in humans, microcephaly has not previously been linked with somatic growth defects(Gilmore and Walsh, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the targeted deletion of one allele of the kinase Dyrk1a in mice resulted in decreased brain volume, and the authors observed reduced neuronal size and dendritic complexity, similar to our observations in 16pdup neurons(Benavides-Piccione et al, 2005; Fotaki et al, 2002). This kinase is involved in regulation of the PI3K/AKT and Ras/MAPK pathways and hence it is likely that its disruption may result in aberrant neuronal differentiation via dysregulation of these pathways(Ji et al, 2015). However, in humans, microcephaly has not previously been linked with somatic growth defects(Gilmore and Walsh, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other CNVs such as the 1q21.1 duplication predispose to ASD and macrocephaly in addition to intellectual disability (ID) and schizophrenia (Mefford et al, 2008; Milone et al, 2016). In contrast, microcephaly is observed in carriers with mutations in DYRK1A along with predisposition for ID, ASD and seizures (Ji et al, 2015). Although both macrocephaly and microcephaly can be associated with ASD, studies demonstrating that the same gene (or pathway) can cause both macrocephaly and microcephaly (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the hippocampus, Dyrk1A heterozygous mice show a significant reduction in hippocampal thickness, accompanied by decreases in cell number in CA1, CA2, CA3, and DG (Arqué et al, 2008). Humans with de novo heterozygous variants of DYRK1A also have congenital microcephaly, structural brain abnormalities, and intellectual disability (Møller et al, 2008; Ji et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…For example, LGDs in CHD8 and DYRK1A have been found in individuals with ID and ASD but as yet have never been observed in unaffected individuals, indicating high penetrance of these mutations 43,44 . Patients with these rare mutations were then extensively phenotyped to identify distinct syndromic subtypes 7880 . In contrast, individual common variants indicate only a small risk for disease and cannot be used for diagnosis.…”
Section: Genetic Architecture Of Asdmentioning
confidence: 99%